2021
DOI: 10.17221/390/2020-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar additions on the soil chemical properties, bacterial community structure and rape growth in an acid purple soil

Abstract: Biochar is considered as a universal conditioner to improve soil quality, but its effects of different addition rates on soil properties, bacterial community structure and plant growth are still unclear, particularly in the typical acid purple soil in the southwest of China. In this study, 110 days of rape growth pot experiment under the application rate of 0.0% rice husk biochar (CK), 0.8% (CT1), 2.0% (CT2) and 4.0% (CT3) to the acid purple soil. Results showed that all biochar additions improved soil pH, soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
(41 reference statements)
3
14
1
Order By: Relevance
“…A meta-analysis of 59 reports published from 2012 to 2021 showed that BC application increased soil pH, cation exchange capacity, and organic carbon by 46%, 20%, and 27%, respectively ( Singh et al., 2022 ). Biochar application to soils also increased the relative abundance of bacteria involved in soil carbon and nitrogen cycles, soil organic carbon decomposition, and plant disease suppression and significantly increased invertase and catalase activities ( Li et al., 2021 ). Biochar application resulted in favorable conditions for soil microorganisms, improving microbial biomass carbon (C mic ) ( Luo et al., 2014 ).…”
Section: Biochar Application Sequestrates Greenhouse Gases Improves S...mentioning
confidence: 99%
“…A meta-analysis of 59 reports published from 2012 to 2021 showed that BC application increased soil pH, cation exchange capacity, and organic carbon by 46%, 20%, and 27%, respectively ( Singh et al., 2022 ). Biochar application to soils also increased the relative abundance of bacteria involved in soil carbon and nitrogen cycles, soil organic carbon decomposition, and plant disease suppression and significantly increased invertase and catalase activities ( Li et al., 2021 ). Biochar application resulted in favorable conditions for soil microorganisms, improving microbial biomass carbon (C mic ) ( Luo et al., 2014 ).…”
Section: Biochar Application Sequestrates Greenhouse Gases Improves S...mentioning
confidence: 99%
“…A significant component in reducing soil losses is the growth of macroaggregates [119]. Biochar can also improve the soil microbial ecology by influencing the community structure and quantity of soil bacteria and regulating the interaction between soil environmental variables and microorganisms [120]. In fine-textured soils, biochar can improve water infiltration and hydraulic conductivity.…”
Section: Effect Of Biochar Application On Soil Propertiesmentioning
confidence: 99%
“…Moreover, RW acts as a water storage module in the green roof, and it reduces the risk of urban flooding and the concentration of nitrogen and phosphorus in the runoff due to its stronger adsorption for nitrogen and phosphorus elements, so it has a wide range of applications in pollution prevention and urban landscape (Vijayaraghavan and Raja, 2014;Choi and Shin, 2019). In addition, RW alters water and nutrient cycling processes in farmland, it indirectly changes the composition and structure of soil microbial communities and key processes such as carbon and nutrient conversion, and then enhances the microbial activity and crop root growth in the root environment, thus supporting photosynthesis and crop growth in the upper part of the plant (Li S. P. et al, 2021;Hawrot-Paw et al, 2022). Therefore, RW may play an excellent role in soil and water conservation, soil remediation and agricultural production, etc (He et al, 2019;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%